Improved Electrochemical Performance of LiNi0.8Co0.15Al0.05O2 Cathode Material by Coating of Graphene Nanodots. Issue 6 (1st April 2019) - He, Xiaoshu; Han, Guokang; Lou, Shuaifeng; Du, Lei; Xu, Xing; Du, Chunyu; Cheng, Xinqun; Zuo, Pengjian; Ma, Yulin; Huo, Hua; Yin, Geping
Abstract : LiNi0.8 Co0.15 Al0.05 O2 cathode material coated with graphene nanodots (GNDs) is designed for the first time to enhance the electrochemical performance. The uniform distribution of GNDs with the size of 5 nm on the LiNi0.8 Co0.15 Al0.05 O2 particle surface can dramatically improve the electronic conductivity. Furthermore, the moderate GNDs coating can provide abundant lithium-ion transportation pathways for the enhanced rate performance. As a result, the GNDs-coated LiNi0.8 Co0.15 Al0.05 O2  with 0.5 wt% coating amount exhibits a high discharge capacity of 150 mAh g −1 at the high rate of 5 C. The novel GNDs coating proposed in this study provides a new strategy to improve the power and energy density for lithium-ion batteries.